Causes of Pneumonia in Children and Modern Possibilities of Prevention - Burkhanovich, Sanakulov Abdulatif (Journal of Science in Medicine and Life, 2024)
Pneumonia in children is an acute infectious lesion of the lung parenchyma and close functional structures of the respiratory system. Pneumonia in children is accompanied by general intoxication, coughing attacks and impaired gas exchange in the lungs. Diagnosis is made during examination: examination, auscultation, laboratory tests and hardware studies. Therapy for pneumonia in children includes the use of drugs with antibacterial, bronchodilator, antipyretic, mucolytic and antihistamine effects. Physiotherapy treatments, exercise therapy and massage are recommended to restore the body's strength after the acute phase.